Friday

March 27, 2015

March 27, 2015

Posted by **Shane** on Monday, June 17, 2013 at 9:38pm.

- Maths -
**Reiny**, Monday, June 17, 2013 at 10:59pma) for arithmetic:

t3 = a+2d = 4/3

t6 = a+5d = 9

subtract them

3d = 23/3

d = 23/9

then a+2(23/9) = 4/3

a = -34/9

first 6 terms are:

-34/9, -11/9 , 4/3 , 35/9 , 58/9 , 9

well, that checked out ok

b) for geometric

t3 = ar^2 = 4/3

t6 = ar^5 = 9

divide them

r^3 = 27/4 = 54/8 , so I can take a nice cube root of the bottom

r = (3/2)(2^(1/3)

then a(9/4)(2^(2/3) = 4/3

a = (16/27) 2^(-2/3)

messy subs , you try them

**Answer this Question**

**Related Questions**

Maths - 1..The first 2 terms of a geometric progression are the same as the ...

Math - A sequence is formed by adding together the corresponding terms of a ...

math - in an arithmetic sequence the common difference is equal to 2.the first ...

Maths - An arithmetic and a geometric sequence have the same first terms.(2).......

math - suppose an arithmetic sequence and a geometric sequence with common ...

math - Determine whether each sequence is arithmetic or geometric. Find the next...

Maths - The first term of an arithmetic sequence is 2. The first, third and ...

Mathematics arithmetic sequence - The sum of second and sixth terms of an ...

Algebra - Determine whether each sequence is arithmetic or geometric. Find the ...

maths - the third term of a geometric sequence is 6 and the sixth term is 3 over...